2017
DOI: 10.1002/ajmg.a.38207
|View full text |Cite
|
Sign up to set email alerts
|

De novo loss‐of‐function variants in STAG2 are associated with developmental delay, microcephaly, and congenital anomalies

Abstract: The cohesin complex is an evolutionarily conserved multi-subunit protein complex which regulates sister chromatid cohesion during mitosis and meiosis. Additionally, the cohesin complex regulates DNA replication, DNA repair, and transcription. The core of the complex consists of four subunits: SMC1A, SMC3, RAD21, and STAG1/2. Loss-of-function mutations in many of these proteins have been implicated in human developmental disorders collectively termed "cohesinopathies." Through clinical exome sequencing (CES) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 37 publications
0
49
0
1
Order By: Relevance
“…Earlier chromosome studies identified several recurrent deletions in patients with CDH, including, e.g., 1q41-42, 8p23.1, and 15q26. Recently, efforts at identifying other genetic causes using large cohorts of patients with CDH have been made [34,35] and several critical CDH genes have been identified such as ZFPM2, GATA4, GATA6 [36,37] and rare variants in other genes, e.g., STAG2 which is implicated in a syndromic form of XLID with microcephaly and a behavioral phenotype [38][39][40]. Complex disorders including CDH with associated LH (and pulmonary hypertension) include Donnai-Barrow syndrome (LRP2), CHARGE syndrome (CHD7), Matthew-Wood syndrome (STRA6), Simpson-Golabi-Behmel syndrome (GPC3), Cornelia de Lange syndrome (NIPBL), and autosomal recessive Fryns Syndrome (PIGN) [32].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier chromosome studies identified several recurrent deletions in patients with CDH, including, e.g., 1q41-42, 8p23.1, and 15q26. Recently, efforts at identifying other genetic causes using large cohorts of patients with CDH have been made [34,35] and several critical CDH genes have been identified such as ZFPM2, GATA4, GATA6 [36,37] and rare variants in other genes, e.g., STAG2 which is implicated in a syndromic form of XLID with microcephaly and a behavioral phenotype [38][39][40]. Complex disorders including CDH with associated LH (and pulmonary hypertension) include Donnai-Barrow syndrome (LRP2), CHARGE syndrome (CHD7), Matthew-Wood syndrome (STRA6), Simpson-Golabi-Behmel syndrome (GPC3), Cornelia de Lange syndrome (NIPBL), and autosomal recessive Fryns Syndrome (PIGN) [32].…”
Section: Discussionmentioning
confidence: 99%
“…The variant was initially classified as a variant of unknown clinical significance based on the American College of Medical Genetics and Genomics variant assessment (Richards et al, ) (Supporting Information Table ). Since then, STAG2 variants have been recently been associated with a new clinical entity (Mullegama et al, ; Soardi et al, ). Based on the effects of the missense variant on the protein structure (Figure c), this variant, p.Lys1009Asn, was reclassified as likely pathogenic.…”
Section: Resultsmentioning
confidence: 99%
“…The first reports of STAG2 copy number variants were identified in 33 males with chromosome Xq25 duplications, involving STAG2, with intellectual disability, behavioral problems, seizures, malar flatness, and prognathism (Bonnet et al, ; Kumar et al, ; Leroy et al, ; Philippe et al, ; Yingjun et al, ). Shortly after, we described three cases of de novo heterozygous STAG2 variants in females associated with a distinct phenotype that affects growth, nervous system development, hearing, and limb formation (Table ) (Mullegama et al, ). Subsequently, a familial STAG2 missense mutation was identified in one family with five affected males.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations